Culture Effects on the Chinese Version Boston Naming Test Performance and the Normative Data in the Native Chinese-Speaking Elders in Mainland China - Li, Yan; Qiao, Yuchen; Wang, Fen; Wei, Cuibai; Wang, Rui; Jin, Hongmei; Xie, Bingxin; You, Jing; Jia, Jianping; Zhou, Aihong (Frontiers in Neurology, 2022)
Background: The Chinese version of Boston Naming Test (BNT-C) is administered in China widely. However, the neuropsychological parameter of BNT-C in native Chinese-speaking elders in mainland China has not been explored systematically. The aim of this study was to explore culture influences on the BNT-C performance and establish norms in native Chinses-speaking elders in Beijing. Methods: A total of 161 native, Chinese-speaking, cognitively normal elders aged ≥55 years were enrolled from communities in Beijing. The BNT-C was conducted to all participants. The internal consistency, participants’ familiarity and naming accuracy were analyzed and compared with data from Chinese areas outside mainland and Americans published previously. The influencing factors and stratified norms for BNT-C were established. Results: The BNT-C showed good internal consistency (α = 0.738). Strong correlation between naming accuracy and object familiarity was found (r = 0.962, P < 0.001). Participants’ familiarity and correct naming rate for many items were notably different between Chinese-speaking elders and English-speaking elders in American. Difference in some items correct naming rate also existed between Beijing, Taiwan and Hongkong. Higher education was associated with higher scores, whereas age and gender had no effect on BNT-C performance. The recommended norms of spontaneous naming scores for elders with education ≤9 years and＞9 years were 14 and 20 respectively. Conclusion: The participants’ familiarity with BNT items differed between different cultures, which further affected the naming accuracy and total scores. The education stratified norms established here are helpful for better application of BNT-C in mainland China.